Upaya Pendekatan Kedokteran Keluarga pada Perempuan Usia 45 Tahun dengan Hipertensi di Aceh Utara - Alya Fadila Husna; Noviana Zara (Inovasi Kesehatan Global, 2025)
Hypertension is a condition where blood pressure is persistently above the normal limit. This condition is a risk factor that can cause damage to vital organs, including the heart, brain, retina, kidneys, aorta, and peripheral blood vessels. This case study aims to describe the implementation of these management efforts in a 45-year-old female patient with hypertension in Blang Dalam Geunteng Village, Nisam District, North Aceh. Mrs. H, a 45-year-old woman, came to the General Clinic of Nisam Community Health Center with a primary complaint of headache since one week before the visit. The headache felt like a throbbing pain throughout the head and was intermittent. This complaint was quite disruptive to the patient's daily activities, especially when doing light household chores. In addition, the patient complained of a throbbing sensation in both eyes that began to be felt simultaneously with the onset of the headache. This complaint appeared mainly when waking up in the morning. The patient has a history of hypertension that has been diagnosed since 2024. Family history shows that the patient's biological mother also suffered from hypertension and one of the patient's siblings was also diagnosed with high blood pressure but had not started treatment. Physical examination showed a blood pressure of 150/90 mmHg. Data were collected through anamnesis, physical examination, supporting procedures, home visits, and family documentation. The holistic assessment included quantitative and qualitative aspects of the initial visit, the process, and the outcome of the visit. Interventions included hypertension education, medication adherence, a healthy lifestyle, and family support for blood pressure management and lifestyle. This case study demonstrates the importance of a holistic and continuous family medicine approach in the management of patients with grade II hypertension, particularly those with familial risk factors.